2014
DOI: 10.1136/neurintsurg-2014-011249
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of short-term total hospital costs and current primary cost drivers of coiling versus clipping for unruptured intracranial aneurysms

Abstract: Total index hospitalization costs for clipping are lower than for coiling. Costs of clipping and coiling are driven by different clinical variables. The cost of coils and devices is the predominant contributor to the higher total costs of coiling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 22 publications
(9 reference statements)
0
37
0
1
Order By: Relevance
“…Факторами риска непол-ного эндоваскулярного выключения являются размер купола более 10 мм, расслаивающие ЦА, расположение в области бифуркации (например, бифуркации СМА и от-ношение размеров шейки к куполу более чем 1:2). Кроме того, за счет эндоваскулярных расходных материалов и повторных ангиограмм эндоваскулярный койлинг зна-чительно дороже, чем клипирование [41].…”
Section: Discussionunclassified
“…Факторами риска непол-ного эндоваскулярного выключения являются размер купола более 10 мм, расслаивающие ЦА, расположение в области бифуркации (например, бифуркации СМА и от-ношение размеров шейки к куполу более чем 1:2). Кроме того, за счет эндоваскулярных расходных материалов и повторных ангиограмм эндоваскулярный койлинг зна-чительно дороже, чем клипирование [41].…”
Section: Discussionunclassified
“…Although, single center investigations have shown a lower hospitalization cost for coiling, 19,22,25,39 a retrospective analysis of the Nationwide Inpatient Sample 23 showed that clipping was associated with higher hospitalization charges for both ruptured and unruptured aneurysms. Utilizing the same national database Bekelis et al, 7,10 developed a predictive model of hospitalization cost for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,11,12,14,15,18,24,26,28,33 Several studies have analyzed the economic aspects of cerebral aneurysm interventions. 19,22,25,27,37,39 However, the generalizability of their findings is limited due to the lack of adjustment for unmeasured confounding. In addition, most investigators have focused only on hospitalization cost, which does not take into account the cost of possible future reintervention in endovascularly treated patients, or the cost of long-term care in patients experiencing complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15][16][17] Several studies have analyzed the economic aspects of cerebral aneurysm interventions. [18][19][20][21][22][23] However, the generalizability of their findings is limited because most authors failed to adjust appropriately for measured or unmeasured confounders. Some are single-center [18][19][20] or international experiences [21][22][23] whereas others have utilized charges as a surrogate for cost 24 and are therefore not reflecting the true financial impact of these procedures.…”
Section: Introductionmentioning
confidence: 99%